2022
DOI: 10.1097/moh.0000000000000713
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac lymphatics: state of the art

Abstract: Purpose of reviewThe beneficial role of cardiac lymphatics in health and disease has begun to be recognized, with both preclinical and clinical evidence demonstrating that lymphangiogenesis is activated in cardiovascular diseases. This review aims to summarize our current understanding of the regulation and impact of cardiac lymphatic remodeling during development and in adult life, highlighting emerging concepts regarding distinguishing traits of cardiac lymphatic endothelial cells (LEC).Recent findingsGeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The cardiac lymphatic vasculature was first described in the 17 th century(Tammela & Alitalo, 2010). To date, studies have demonstrated the role of the lymphatic system only in embryonic heart development and cardiac health in adults(Brakenhielm & Alitalo, 2019; Heron, Ratajska, & Brakenhielm, 2022; Klotz et al, 2015). Cardiac lymphatics can take up inter-tissue fluid and transport immune cells through highly branched, blunt, open-ended lymphatic capillaries, to the lymph nodes near the thoracic ducts and, finally, into the superior vena cava(Huang, Lavine, & Randolph, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The cardiac lymphatic vasculature was first described in the 17 th century(Tammela & Alitalo, 2010). To date, studies have demonstrated the role of the lymphatic system only in embryonic heart development and cardiac health in adults(Brakenhielm & Alitalo, 2019; Heron, Ratajska, & Brakenhielm, 2022; Klotz et al, 2015). Cardiac lymphatics can take up inter-tissue fluid and transport immune cells through highly branched, blunt, open-ended lymphatic capillaries, to the lymph nodes near the thoracic ducts and, finally, into the superior vena cava(Huang, Lavine, & Randolph, 2017).…”
Section: Introductionmentioning
confidence: 99%